Detection of p53 codon 249 mutation in Nigerian patients with hepatocellular carcinoma using a novel evaluation of cell-free DNA (2008)
Objectives: This case-control study was done to determine the association and prevalence of p53 codon 249 mutation using cell-free DNA in the plasma of patients with hepatocellular carcinoma (HCC) in South-Western Nigeria. Method: Eighty-five adults with HCC and seventy-seven age and gender matched controls without evidence of liver disease or malignancy involving any part of the body, were recruited. Plasma DNA was analyzed for p53 codon 249 by restriction fragment length polymorphism. Patient evaluation was done by means questionnaire interview, clinical examination, laboratory and radiological tests. The prevalence of the p53 codon 249 mutation was expressed as a percentage amplifiable DNA samples analyzed from HCC patients while that of controls was expressed in the same way. Fisher’s exact test or the student t-test where appropriate were used to assess statistical significance of prevalence between both groups as well as comparison of some characteristics in the HCC cases between those who had codon 249 mutation and those who did not. Associations between the various parameters assessed were determined by odds ratio and significant difference was specified at p < 0.05. Results: p53 codon 249 mutation was present in 6 (7.6%) of the 79 samples from the HCC patients with amplifiable plasma DNA while none (i.e. 0%) of the 73 samples with amplifiable plasma DNA from the controls had this mutation. This prevalence is significantly higher among HCC patients than controls (0.029). The mutation was also found to be significantly associated with HCC (odds ratio = 2.00; 95% C I: 1.70 – 2.35). Conclusion: The prevalence of the p53 codon 249 mutation from plasma DNA of hepatocellular carcinoma patients is significantly higher than among controls in South-Western Nigeria and the presence of this mutation is significantly associated with HCC in this region.